Effects of integrated reporting on corporate disclosure practices regarding the capitals and performance - Alina Almășan; Cristina Circa; Mădălina Dumitru; Raluca Gina Gușe; Dragoș Marian Mangiuc (Amfiteatru Economic Journal, 2019)
Integrated reporting promotes changing the internal processes of companies to generate improved performance. One way toward this goal is to use integrated thinking as a tool to achieve a "better understanding of the factors that materially affect an organization's ability to create value over time", that is the six capitals, as suggested by the International Integrated Reporting Council. Our goal is to identify 'effects of learning' in the field of integrated reporting on the performance and reporting practices of companies. More specifically, we aim to identify how and to what extent integrated thinking translated into their reporting practices and performance, while companies implemented the International Integrated Reporting Framework. Therefore, we analyse and compare the reporting practices and performance of European companies included in the International Integrated Reporting Council's Pilot Program for two moments in time: 2013 and 2016. We use a set of nineteen indicators, considered as the most important for the presentation of the six capitals. Thus, we provide insights about how integrated reports disclose information concerning the capitals. Results show improvements in performance and the diversification of indicators disclosed in the reports. However, changes are not exclusively attributable to integrated reporting; reporting experience is also a contributing factor. The study contributes to the literature on the impact of integrated reporting in practice.
Keywords: M14; Q56; 330; Integrated reporting; integrated thinking; capitals; performance; key performance indicators